Mercury - Daily, Robert (New York : F. Watts, 1994)
Provides facts and information about the planet Mercury including ancient beliefs, when the planet was discovered, and a day on Mercury.
Includes bibliographical references (p. 61) and index.
Wilson's Junior High School
Appraisal-Science Books for Young People
5.9
5-8
Keywords: Mercury (Planet) -- Juvenile literature; Mercury (Planet); Mercury (Planet)